THE EFFECTIVENESS OF CAREER GUIDANCE PROGRAM FOR PSYCHOLOGY STUDENTS - Monika Monika (IJIET (International Journal of Indonesian Education and Teaching), 2018)
Making a career decision is a complex process. Although some people make decision easily, others face difficulties in making their career decision. Therefore, identifying their difficulties in career decision-making process is an essential step to provide students needs in their career planning. According to Gati, Krausz, and Osipow (1996), the proposed taxonomy of career decision-making difficulties was developed through interaction and sequential interplay between theoretical considerations and empirical testing. Specifically, in the proposed taxonomy the difficulties are divided into three major categories. The first major category is Lack of Readiness. Then the second and the third major categories are Lack of Information and Inconsistent Information. The participants of this study were 95 psychology students divided in two groups (experimental and control groups). The aim of this study is to describe career decision-making in psychology students and to determine the difference of career decision-making difficulties in students with different semesters. The result of this study shows that The Career Guidance Program is effective for decreasing difficulties of career decision-making (lack of information, inconsistent information, and total difficulty), but less effective to decrease the lack of readiness.DOI: https://doi.org/10.24071/ijiet.2018.020212